2004
DOI: 10.1063/1.1665323
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption energies of molecular oxygen on Au clusters

Abstract: The adsorption properties of O(2) molecules on anionic, cationic, and neutral Au(n) clusters (n=1-6) are studied using the density functional theory (DFT) with the generalized gradient approximation (GGA), and with the hybrid functional. The results show that the GGA calculations with the PW91 functional systemically overestimate the adsorption energy by 0.2-0.4 eV than the DFT ones with the hybrid functional, resulting in the failure of GGA with the PW91 functional for predicting the adsorption behavior of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
126
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(160 citation statements)
references
References 31 publications
33
126
0
1
Order By: Relevance
“…These structures are in a good agreement with those reported in previous theoretical studies; see, e.g., Refs. 32,56,57,58,59 In order to obtain the most stable configuration of C 2 H 4 adsorbed on neutral, anionic and cationic gold clusters, we have created a large number of starting geometries by adding C 2 H 4 molecule in different positions (up to 30) on the surface of the most stable cluster and up to eight isomer structures of the corresponding Au n , Au …”
Section: Theoretical Methodsmentioning
confidence: 99%
“…These structures are in a good agreement with those reported in previous theoretical studies; see, e.g., Refs. 32,56,57,58,59 In order to obtain the most stable configuration of C 2 H 4 adsorbed on neutral, anionic and cationic gold clusters, we have created a large number of starting geometries by adding C 2 H 4 molecule in different positions (up to 30) on the surface of the most stable cluster and up to eight isomer structures of the corresponding Au n , Au …”
Section: Theoretical Methodsmentioning
confidence: 99%
“…According to the Bader analysis, the charge localized on the O 2 adsorbed in on-top configuration is -0.92e, where e is an elementary charge. Such mechanism of the charge-transfer-mediated activation of O 2 has been intensively studied for O 2 adsorbed on metal clusters; see, e.g., refs [11,16,17,19,[21][22][23][24][25][26][27] and references therein. Adsorption of O 2 on h-BN/Ni(111) in a bridge configuration results in a further population of the down-spin 2π * orbital which becomes completely occupied and lies below the Fermi level.…”
Section: Adsorption Of O 2 On a Free And Metal Supported H-bn Monolayermentioning
confidence: 99%
“…In the case of O 2 adsorption on the V B defect in h-BN monolayer oxygen molecule is partially dissociated with the distance between O atoms of 1.79 A. Activation of the adsorbed O 2 is accompanied by the charge transfer from the defected surface to the oxygen. Such mechanism of the charge-transfer-mediated activation of O 2 has been intensively studied for O 2 adsorbed on metal clusters; see, e.g., [11,18,[21][22][23][24][25][26][27] and references therein. As it was discussed in [13] the h-BN monolayer with B N , V N , and V B defects can not be a good catalyst due to the strong bonding of O 2 to the surface.…”
Section: Introductionmentioning
confidence: 99%
“…The predicted global minimum with O 2 bridging between two Au atoms is in accordance with most recent published theoretical work, 10,11 while older studies reported the end-on structure to be the global minimum. 12,27,28 Some studies used the end-on species as the reactant rather than the global minimum bridging structure. The latter species is the starting structure ͑reactant͒ presented as the first minimum ͑min1, the first point along the x-axis͒ in Fig.…”
Section: Resultsmentioning
confidence: 99%